A Novel [OSSO]‐Type Chromium(III) Complex as a Versatile Catalyst for Copolymerization of Carbon Dioxide with Epoxides. Issue 24 (15th April 2020) - Della Monica, Francesco; Paradiso, Veronica; Grassi, Alfonso; Milione, Stefano; Cavallo, Luigi; Capacchione, Carmine
Abstract: A new chromium(III) complex, bearing a bis‐thioether‐diphenolate [OSSO]‐type ligand, was found to be an efficient catalyst in the copolymerization of CO2 and epoxides to achieve poly(propylene carbonate), poly(cyclohexene carbonate), poly(hexene carbonate) and poly(styrene carbonate), as well as poly(propylene carbonate)(cyclohexene carbonate) and poly(propylene carbonate)(hexene carbonate) terpolymers. Abstract : The synthesis of "green" polycarbonates from carbon dioxide and epoxides was accomplished by using a chromium catalyst bearing an [OSSO]‐ligand. The unprecedented versatility of the complex and its efficiency in reactions involving linear and internal epoxides led obtaining polycarbonates with different architectures. Catalytic behavior was rationalized through DFT calculations.